2019
DOI: 10.1128/mbio.02323-18
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Human Papillomavirus Oncogene Expression under Hypoxia Is Mediated by PI3K/mTORC2/AKT Signaling

Abstract: Oncogenic HPV types are major human carcinogens. Under hypoxia, HPV-positive cancer cells can repress the viral E6/E7 oncogenes and induce a reversible growth arrest. This response could contribute to therapy resistance, immune evasion, and tumor recurrence upon reoxygenation. Here, we uncover evidence that HPV oncogene repression is mediated by hypoxia-induced activation of canonical PI3K/mTORC2/AKT signaling. AKT-dependent downregulation of E6/E7 is only observed under hypoxia and occurs, at least in part, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 78 publications
(120 reference statements)
3
62
0
Order By: Relevance
“…All gynecological cancers have been reported to show an overexpression of HIF in a hypoxic environment, but data suggest that HIF enables specific isoforms of the PKC family to accumulate. As the cascade continues, this leads to an mTORC2-mediated effect currently reported only in cervical cancer [94,95]. Therefore, a further inquiry to be opened by this review is the role played by hypoxia downstream in the mTORC2 cascade.…”
Section: Resultsmentioning
confidence: 98%
“…All gynecological cancers have been reported to show an overexpression of HIF in a hypoxic environment, but data suggest that HIF enables specific isoforms of the PKC family to accumulate. As the cascade continues, this leads to an mTORC2-mediated effect currently reported only in cervical cancer [94,95]. Therefore, a further inquiry to be opened by this review is the role played by hypoxia downstream in the mTORC2 cascade.…”
Section: Resultsmentioning
confidence: 98%
“…Nonetheless, a recent study showed that HPV-16 E7 can attenuate pAKT signalling [35]. In addition, hypoxic AKT activation is observed under conditions of E6/E7 repression [36], which indicates that the hypoxic AKT activation is regulated by Fig. 3 Over expression of GCN5 rescues DNA replication reduction induced by WDHD1 depletion.…”
Section: Discussionmentioning
confidence: 96%
“…Hypoxia-induced effect of the PI3K/m-TOR/AKT pathway is countered by increased activity of HIF1α which is also hypoxia dependent [65]. HIF1α through regulated in development and DNA damage response 1 (REDD1) inhibits mTORC1 signalling and stops senescence in case E6/E7 is repressed [65]. This proves that mTORC2 is still active in hypoxic environment, whereas mTORC1 shows susceptibility to oxygen shortage [66].…”
Section: Pi3k/akt/mtor Pathway Disruption By E6/e7mentioning
confidence: 92%
“…However, this was observed only for normoxic HPVpositive cells [64]. Hypoxia-induced effect of the PI3K/m-TOR/AKT pathway is countered by increased activity of HIF1α which is also hypoxia dependent [65]. HIF1α through regulated in development and DNA damage response 1 (REDD1) inhibits mTORC1 signalling and stops senescence in case E6/E7 is repressed [65].…”
Section: Pi3k/akt/mtor Pathway Disruption By E6/e7mentioning
confidence: 99%
See 1 more Smart Citation